2003
DOI: 10.1046/j.1461-0248.2003.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Covert infections as a mechanism for long‐term persistence of baculoviruses

Abstract: The prevalence of pathogens in wild populations has often been estimated by the appearance of overt symptoms in the host, and this is typically used as the sole gauge of the impact of the pathogen on host dynamics. However, the development of molecular methods has increased the sensitivity with which we can detect asymptomatic infections. Baculoviruses are insect pathogens that, like many microparasites, are usually only found when their hosts reach outbreak densities, when a disease epizootic occurs. Conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 34 publications
(38 reference statements)
4
120
1
2
Order By: Relevance
“…Our findings are similar to those of Eastwell et al (1999), who detected latent virus in laboratory cultures, and in 23% of larvae of codling moth populations from British Columbia, using the PCR reaction. Application of PCR permitted Burden et al (2003) to demonstrate a higher rate (50 to 100%) of latent infection in natural cabbage moth populations in England, and, similar to our results, the virus was present in insects from geographically remote regions. Moreover, they demonstrated that the viral infection rate of these insects when reared in the laboratory (under conditions without external viral contamination) usually did not decrease over the five generations during which they were observed.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are similar to those of Eastwell et al (1999), who detected latent virus in laboratory cultures, and in 23% of larvae of codling moth populations from British Columbia, using the PCR reaction. Application of PCR permitted Burden et al (2003) to demonstrate a higher rate (50 to 100%) of latent infection in natural cabbage moth populations in England, and, similar to our results, the virus was present in insects from geographically remote regions. Moreover, they demonstrated that the viral infection rate of these insects when reared in the laboratory (under conditions without external viral contamination) usually did not decrease over the five generations during which they were observed.…”
Section: Discussionsupporting
confidence: 88%
“…Such vertically transmitted infections are mainly if not exclusively covert, which might present a mechanism for long-term persistence in the honeybee population as has also been described for other insect viruses (Bonsall et al, 2005;Burden et al, 2003;de Miranda & Genersch, 2010;Hails et al, 2008). Only in association with the ectoparasitic mite V. destructor have overt outbreaks of DWV infection, characterized by deformed wings as the most prominent symptom, been recorded (Ball, 1989;Ball & Allen, 1988;Bowen-Walker et al, 1999;Martin, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…Molecular techniques have been based on the detection of viral DNA or mRNA transcripts (3,(11)(12)(13)32) or, more recently, proteomics-based techniques (1). The mechanisms by which the virus persists in the cells of sublethally infected insects without triggering apoptosis remains unclear, although advances in the field of microRNA research may soon shed light on this issue (33).…”
mentioning
confidence: 99%
“…The mechanisms by which the virus persists in the cells of sublethally infected insects without triggering apoptosis remains unclear, although advances in the field of microRNA research may soon shed light on this issue (33). Covert infections are believed to persist in one of two forms: as a latent infection in which the virus is not replicating and transcriptional activity is minimal, or as a sublethal infection in which the virus is transcriptionally active and replication occurs at a low level (2,3,9). Compared to healthy conspecifics, sublethally infected insects can experience slower development rates, lower pupal and adult body weights, reduced reproductive capacity, or altered preoviposition period (26,30,38).…”
mentioning
confidence: 99%